Reconstruction of Islamic Religious Education Curriculum: A Qualitative Study between Theoretical and Implementation Perspectives - Mella Sophya (JELCre - Journal of Education and Learning Creativity, 2025)
Islamic Religious Education (PAI) plays a strategic role in shaping students who possess strong faith, moral character, and Islamic values. As a core component of the educational system, the PAI curriculum is expected to integrate Islamic theoretical foundations with contextual and effective instructional practices. However, numerous studies indicate a persistent gap between the theoretical design of the PAI curriculum and its practical implementation. This study aims to examine and reconstruct the Islamic Religious Education curriculum by integrating theoretical and practical perspectives. Employing a qualitative descriptive approach, this research utilizes a library research method by analyzing reputable national andi nternationally journal articles published over the last ten years. Data were analyzed through data reduction, data presentation, and narrative conclusion drawing. The findings reveal that the reconstruction of the PAI curriculum should emphasize the integration of curriculum planning, instructional strategies, and contextual evaluation while adapting to social and technological developments. This study contributes conceptually by proposing an integrative and applicable framework for reconstructing the PAI curriculum, which may serve as a reference for developing Islamic education curricula that are responsive to contemporary educational challenges. Islamic Religious Education (PAI) plays a strategic role in shaping students who possess strong faith, moral character, and Islamic values. As a core component of the educational system, the PAI curriculum is expected to integrate Islamic theoretical foundations with contextual and effective instructional practices.  However, numerous studies indicate a persistent gap between the theoretical design of the PAI curriculum and its practical implementation. This study aims to examine and reconstruct the Islamic Religious Education curriculum by integrating theoretical and practical perspectives. Employing a qualitative descriptive approach, this research utilizes a library research method by analyzing reputable national and international journal articles published over the last ten years. Data were analyzed through data reduction, data presentation, and narrative conclusion drawing. The findings reveal that the reconstruction of the PAI curriculum should emphasize the integration of curriculum planning, instructional strategies, and contextual evaluation while adapting to social and technological developments. This study contributes conceptually by proposing an integrative and applicable framework for reconstructing the PAI curriculum, which may serve as a reference for developing Islamic education curricula that are responsive to contemporary educational challenges.